2021
DOI: 10.1111/bpa.12922
|View full text |Cite
|
Sign up to set email alerts
|

Distinct circular RNA expression profiles in pediatric ependymomas

Abstract: Pediatric ependymomas frequently develop in the cerebellum and are currently treated using non-specific therapies, in part, because few somatically mutated driver genes are present, and the underlying pathobiology is poorly described. Circular RNAs (circRNAs) constitute as a large class of primarily non-coding RNAs with important roles in tumorigenesis, but they have not been described in pediatric ependymomas. To advance our molecular understanding of ependymomas, we performed Next Generation Sequencing of rR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…With a wide use for transcriptomic studies, nCounter has been recently adapted for the detection of circRNAs using a specific probe design where sequences span the circRNAs junction site [ 19 ]. On this regard, some authors have proved the benefits of this technology to study circRNA subcellular distribution [ 22 ], or elucidate the potential roles in skin [ 23 , 24 ] or brain diseases [ 25 ]. However, to date, no one has explored this platform in FFPE samples for the development of lung cancer signatures.…”
Section: Discussionmentioning
confidence: 99%
“…With a wide use for transcriptomic studies, nCounter has been recently adapted for the detection of circRNAs using a specific probe design where sequences span the circRNAs junction site [ 19 ]. On this regard, some authors have proved the benefits of this technology to study circRNA subcellular distribution [ 22 ], or elucidate the potential roles in skin [ 23 , 24 ] or brain diseases [ 25 ]. However, to date, no one has explored this platform in FFPE samples for the development of lung cancer signatures.…”
Section: Discussionmentioning
confidence: 99%
“…A vast group of mostly non-coding circular RNAs has important roles in tumorigenesis. Disease stage, outcome, age, and gender were associated with cirRNA patterns [ 42 ]. CircRNAs are a type of noncoding RNAs (ncRNAs) that have a continuous closed loop rather than 5′ caps and 3′ tails [ 21 , 43 ].…”
Section: Circular Rnamentioning
confidence: 99%
“…CircRNAs were numerous and even substantially produced in mammalian cells compared to the host gene’s linear RNA isoforms [ 21 ]. CircRNAs have emerged as a diverse class of endogenous RNAs with primarily non-coding functions essential for development and illness [ 42 ]. However, increased interest in circRNA has emerged in recent years as a result of their increasing operations in human biology [ 45 , 46 , 47 , 48 ].…”
Section: Circular Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that circ-SKA3 and circ-DTL have key carcinogenic effects in the occurrence and development of medulloblastoma [ 43 ]. Ahmadov et al found that ependymoma specifically upregulated circRNA derived from RMST, LRBA, WDR78, DRC1 and BBS9 genes through Next Generation Sequencing, but their results still need experiments to prove [ 44 ].…”
Section: Circrna and Common Smts In Childrenmentioning
confidence: 99%